AB0397 GO.A.RE.L. (Golimumab in Apulian Real-Life Patients) Study. Preliminary Data from Golimumab Therapy in Patients Affected with Polyarthritis. A Multicentre Experience in Apulia (Southern Italy). (10th June 2014) - Santo, L.; Semeraro, A.; Zuccaro, C.; Anelli, M.G.; Bucci, R.; D'Alessandro, G.; Casilli, O.; Quarta, L.; Carlino, G.; Cacciapaglia, F.; Falappone, P.C.F.; Serafino, L.; et al.
Abstract : Background: Golimumab has proven to be effective and safe in randomized clinical trials Go-Forward, Go-After, Go-Before and Go-More for Rheumatoid Arthritis (RA), Go-Raise for Ankylosing Spondlylitis (AS), Go-Reveal for Psoriatic Arthritis (PsA) for which patients have been accurately selected. Instead, data from Golimumab therapy in patients from daily clinical practice, where comorbidities, poly-therapy, severe clinical manifestations, systemic extra-articular involvement may influence drug effectiveness or safety, are still lacking. Objectives: The scope of this multicentric spontaneous observational study is to evaluate the effectiveness and safety of Golimumab – the newest anti-TNFa monoclonal antibody – in unselected patients who are affected with chronic polyarthritis – RA and Spondyloarthritis (SpA) - and undergoing the treatment with Golimumab in 11 rheumatologic clinical Units of Apulia (Southern Italy). Methods: 211 patients (69 males and 142 females) affected with polyarthritis (44 RA, 167 SpA, including 91 PsA and 76 axial-SpA) have been enrolled. Mean age was 50.5 (21-86) in SpA and 56.1 (21-81) in RA, with mean disease duration of 7 years in SpA and 9.31 in RA, respectively. Safety and effectiveness were established as primary end-points following 12 months for RA and 24 months for SpA. Effectiveness was assessed by 28-joints disease activity (DAS28), clinical disease activity index (CDAI) and Health Assessment Questionnaire (HAQ) in RA patients, whereas Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), C-reactive protein Ankylosing Spondylitis Disease Activity Score (ASDAS) and DAS28 were used in axial-SpA and PsA. ANOVA for repeated measures has been used for statistical intra-group comparisons between baseline and different follow-up points. Results: 8 patients out of 211 were lost during follow-up; 34 patients (16, 7%) out of 203 interrupted Golimumab treatment due to inefficacy; 13 (6, 4%) presented major side effects causing drug interruption; 5 (2, 4%) showed minor side effects that did not demand the treatment interruption. Table 1 and 2 show treatment effectiveness. Conclusions: Preliminary results confirm a good effectiveness and safety of Golimumab in patients with RA or SpA in standard care settings. Further analysis to assess the influence of obesity and other comorbidities, or combination therapy with standard drugs are ongoing. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1923